1996
DOI: 10.1002/anie.199624281
|View full text |Cite
|
Sign up to set email alerts
|

Novolak‐Diazoquinone Resists: The Imaging Systems of the Computer Chip

Abstract: Si02 + 4 HF -+ SiF4 + 2H20S o m e of the fundamental steps of microlithography (coating, irradiation, development of the film with base, removal of the Si02 layer) and on the right the chemical processes involved. This year some twenty billion integrated circuits will be produced worldwide. Almost all (98%) of them will be made with a photosensitive varnish, the photo resist, that allows the transfer of a fine line-pattern from an original transparency onto a silicon wafer. This photoresist has two components:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…This second effect is known qualitatively but was not tested quantitatively. E.g., Arnošt Reiser et al (1996) found that some molecules served as local heaters after their activation by light beam absorption and started to promote the following chemical reactions.…”
Section: The Prismatic Rainbow -"Iris Trigonia"mentioning
confidence: 99%
“…This second effect is known qualitatively but was not tested quantitatively. E.g., Arnošt Reiser et al (1996) found that some molecules served as local heaters after their activation by light beam absorption and started to promote the following chemical reactions.…”
Section: The Prismatic Rainbow -"Iris Trigonia"mentioning
confidence: 99%
“…Novolak is obtained through a polycondensation reaction between formaldehyde and cresols [4,14]. The novolak resin is photochemically inert at 436 and 365 nm, and is easily soluble in basic developers due to its phenolic OH groups, but upon addition of naphthoquinone the dissolution rate decreases dramatically [15,16].…”
Section: Photolithography With Nonamplified Resistsmentioning
confidence: 99%
“…After the novolak films containing DNQ are exposed to UV radiation, their solubility increases by a few orders of magnitude, the dissolution rate becoming even higher than in the case of novolak films without any dissolution inhibitor. The explanation of this phenomenon was sought in the photochemistry of DNQ, but no clear picture was offered until relatively recently [15,16]. When exposed to UV radiation, upon absorption of photons diazonaphthoquinone eliminates N 2 forming a reactive carbene biradical that undergoes Wolff rearrangement to form a ketene (Scheme 12.1).…”
Section: Photolithography With Nonamplified Resistsmentioning
confidence: 99%
“…Diazonaphthoquinones are compounds widely used in the fabrication of integrated circuits in microlithography [4][5][6][7] where they are embedded in a novolak matrix (a phenol-formaldehyde condensation polymer). Exposed to radiation the diazoquinones release molecular nitrogen undergoing a ring contraction, the so-called Wolff rearrangement.…”
Section: Introductionmentioning
confidence: 99%